Business Risk Management Using Strengths Weaknesses Opportunities Treats in Small Business - Mekar Meilisa Amalia; Kraugusteeliana; Baren Sipayung; Indra Rustiawan; Bambang (Institute of Computer Science (IOCS), 2023)
In terms of product marketing, the post-pandemic transition to the new normal era has a significant impact on MSMEs, specifically a fall in demand, which substantially disrupts economic activity. Of course, the impact of diminished product demand poses a risk for MSMEs engaged in these commercial operations. Risk management is required to lead, identify, and find solutions to hazards. The significance of understanding risk management in marketing has a substantial impact on MSMEs in choosing effective marketing strategies for service quality, product diversity, and increasing sales turnover. As a result, the research purpose is to analyze risk management in MSME enterprises using SWOT analysis, in order to propose methods for MSMEs in identifying opportunities and strengths in business operations. Risk management investigation revealed operational risks in MSMEs when running a firm, raw material supply risks, and marketing risks, all of which are crucial in reaching a bigger market segmentation and meeting marketing targets. The SWOT analysis results can provide strategic recommendations for MSMEs that produce 9 strategies based on studying MSMEs' strengths and possibilities in facing global competition and maintaining enterprises to further improve sales turnover.